A Contact SPH Method with High-Order Limiters for Simulation of Inviscid Compressible Flows (Communications in Computational Physics, 2014)
In this paper, we study a class of contact smoothed particle hydrodynamics(SPH) by introducing Riemann solvers and using high-order limiters. In particular, apromising concept of WENO interpolation as limiter is presented in the reconstructionprocess. The physical values relating interactional particles used as the initial values ofthe Riemann problem can be reconstructed by the Taylor series expansion. The contactsolvers of the Riemann problem at contact points are incorporated in SPH approximations. In order to keep the fluid density at the wall rows to be consistent with that ofthe inner fluid wall boundaries, several lines of dummy particles are placed outsideof the solid walls, which are assigned according to the initial configuration. At last,the method is applied to compressible flows with sharp discontinuities such as thecollision of two strong shocks and the interaction of two blast waves and so on. Thenumerical results indicate that the method is capable of handling sharp discontinuityand efficiently reducing unphysical oscillations.